2007
DOI: 10.1245/s10434-006-9318-z
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Resection Independently Improves Long-Term Survival in Patients with T1–T2 Hepatocellular Carcinoma

Abstract: Anatomic resection independently improves long-term survival in patients with T1-T2 hepatocellular carcinoma, probably because of the clearance of venous tumor thrombi within the resected domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
133
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(138 citation statements)
references
References 37 publications
5
133
0
Order By: Relevance
“…The decision to use neoadjuvant chemotherapy was made by the Institutional Cancer Committee of Niigata University Medical and Dental Hospital. Indications for neoadjuvant chemotherapy included multiple hepatic tumors or a solitary tumor >3 cm in diameter, because these preoperative factors are closely associated with vascular invasion or poor post-resection survival (15)(16)(17). In the current series, 16 patients received neoadjuvant chemotherapy, which consisted of hepatic arterial infusion of a fine-powder formulation of cisplatin (IA-call ® , Nippon Kayaku, Co., Ltd., Tokyo, Japan; recommended dose of 65 mg/m 2 ) under the guidance of hepatic angiography.…”
Section: Patient Population From March 2007 Through Decembermentioning
confidence: 99%
See 2 more Smart Citations
“…The decision to use neoadjuvant chemotherapy was made by the Institutional Cancer Committee of Niigata University Medical and Dental Hospital. Indications for neoadjuvant chemotherapy included multiple hepatic tumors or a solitary tumor >3 cm in diameter, because these preoperative factors are closely associated with vascular invasion or poor post-resection survival (15)(16)(17). In the current series, 16 patients received neoadjuvant chemotherapy, which consisted of hepatic arterial infusion of a fine-powder formulation of cisplatin (IA-call ® , Nippon Kayaku, Co., Ltd., Tokyo, Japan; recommended dose of 65 mg/m 2 ) under the guidance of hepatic angiography.…”
Section: Patient Population From March 2007 Through Decembermentioning
confidence: 99%
“…A hepatectomy procedure was selected for each patient, taking the primary tumor status (size, number, location), the hepatic functional reserve, and the patient's general condition into account (16). In the current study, the term 'major hepatectomy' indicated formal hemihepatectomy or more extensive resection, whereas less extensive hemihepatectomy was designated 'minor hepatectomy'.…”
Section: Patient Population From March 2007 Through Decembermentioning
confidence: 99%
See 1 more Smart Citation
“…Because HCC has a high propensity to invade the intrahepatic vascular structures and spreads mainly via the closest portal veins [9,10], anatomic resection (AR) including systematic removal of the tumor-bearing portal territories was proposed in the 1980s as a theoretically curative surgical procedure for HCC to eradicate potential micrometastases surrounding tumors [11]. Some studies [5,[12][13][14][15] have demonstrated the superiority of AR over non-anatomic resection (NAR) for HCC. However, the optimum liver resection technique in patients with liver dysfunction remains controversial, and there is no clear evidence that AR results in better long-term survival than does NAR [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding method of hepatectomy, the EASL recommends anatomical resection and, although some studies17, 18, 19, 20 have reported survival benefits with anatomical resection, others21, 22, 23, 24 have been unable to do so. Non‐anatomical resection (NAR) is an attractive treatment option for patients with cirrhotic livers, so a comparison of NAR and RFA seems appropriate in the context of achieving local control.…”
Section: Introductionmentioning
confidence: 99%